Patient evaluations of the interpersonal care experience (ICE) in U.S. hospitals: A factor analysis of the HCAHPS survey - Geoffrey Silvera; Jonathan Clark (The Beryl Institute, 2016)
The Hospital Consumer Assessment of Healthcare Providers and Systems survey (HCAHPS) is widely used to evaluate patients' perceptions of their inpatient healthcare experiences. The HCAHPS is organized into 10 measures: six composite measures, two individual measures, and two global measures.1 In prior research on the link between patients' care experiences and hospital's quality and cost outcomes, scholars have grouped these measures in a variety of ways. The evident lack of consistency in these groupings along with the persistent lack of empirical justification for these groupings suggests a need to empirically examine the relational structure of HCAHPS measures. Accordingly, the purpose of this study is to determine the degree to which patient care evaluations captured by HCAHPS reflect unmeasured aspects of the patient experience. We use two-step factor analytic process on a nationally representative split sample of HCAHPS performance from 2007-2011. The results of the analysis reveal a single latent factor consisting of five measures that correspond conceptually to patients' evaluations of care provider behaviors during their interpersonal interactions with them. We label this factor Interpersonal Care Experience (I.C.E) and argue that it may prove useful in future practical and scholarly explorations of the link between patient experience and other performance outcomes.